Three-dimensional digital model of the facial nerve assisted in the excision of benign parotid tumors based on 3D-DESS-WE-MRI - Chunshi Tong; Shuwen Luo; Zhonglin Li; Yonghui Dong; Zhenhui Liu; Xin Meng; Zhi Zou; Liwei Peng (Scientific Reports)
Abstract This study proposes a novel surgical technique for the excision of benign parotid tumors, utilizing a extracapsular dissection guided by a three dimensional digital model of the facial nerve(3DFN-ECD) and compares its clinical efficacy with the extracapsular dissection (ECD) method. This prospective study included 68 patients with benign parotid tumors. The control group (40 patients) received the ECD treatment, while the experimental group (28 patients), underwent the 3DFN-ECD approach proposed in this study. Preoperative three-dimensional double-echo steady-state water excitation sequence (3D-DESS-WE) of MRI was employed to visualize the tumor and facial nerve, and the Mimics software was used to reconstruct a three-dimensional digital model of the facial nerve and parotid tumor. The surgical incision and facial nerve dissection were planned based on the relationship between the tumor and the facial nerve. Postoperative facial nerve function and aesthetic outcomes of the incisions were compared between the two surgical techniques. There was no significant difference in the postoperative complications between the two groups. Postoperative facial nerve function scores in the 3DFN-ECD group were significantly higher than those in the control group at 1 week (p < 0.001) and 4 weeks (p < 0.001). The incidence of temporary facial nerve paralysis was significantly lower in the 3DFN-ECD group (P = 0.036), and the visual analogue scale score for aesthetic outcomes of the surgical incision was significantly improved (p < 0.001). The novel 3DFN-ECD surgical approach proposed in this study significantly reduces the risk of facial nerve injury and improves the aesthetic outcomes of the parotid tumor surgical incision.